The Effect of Using Virtual Laboratory on Grade 10 Students’ Conceptual Understanding and their Attitudes towards Physics - Malak Abou Faour; Zalpha Ayoubi (Journal of Education in Science, Environment and Health, 2018)
This study investigated the effect of using (VL) on grade 10 students’ conceptual understanding of the direct current electric circuit and their attitudes towards physics. The research used a quantitative experimental approach. The sample of the study was formed of 50 students of the tenth grade, aged 14 to 16 years old, of an official secondary school in Mount Lebanon. Participants were randomly assigned into two groups of 25 students each. The experimental group was taught using VL, where experimental activities were conducted through Circuit Construction Kit developed by the PhET simulations. However, the control group was taught through interactive demonstrations using real laboratory equipment. Both groups were pre and post-tested by means of two instruments: ―Determining and Interpreting Resistive Electric current Concepts test‖ (DIRECT) and ―Physics Attitude Scale‖ (PAS). The data analysis of the DIRECT test scores showed that, after 10 weeks, the conceptual understanding of the direct current electric circuit had markedly improved in both groups. However, the mean score of the experimental group was significantly higher than that of the control group. On the other hand, there was no significant difference in students' attitudes towards physics between the two groups.